2018
DOI: 10.1037/mot0000065
|View full text |Cite
|
Sign up to set email alerts
|

Kicking the habit: Why evidence for habits in humans might be overestimated.

Abstract: Researchers typically classify behavior as habitual if it occurs independently of changes in the value of its outcomes (revaluation test) or the impact it has on those outcomes (contingency degradation test). We argue that these tests are valid only if they (a) are sufficiently sensitive and (b) target the outcomes that might actually control behavior. These criteria resemble the sensitivity and information criteria that are widely adopted in research on learning without awareness. We argue that past and futur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
104
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4
2

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 16 publications
3
104
0
1
Order By: Relevance
“…Indeed, column 7 shows a perfect correspondence between impaired explicit contingency knowledge and impaired devaluation performance. In numerous human learning tasks, explicit knowledge of task contingencies is necessary for accurate performance, that is, participants who have impaired contingency knowledge perform less accurately in these tasks [204][205][206][207][208][209]. The implication is that drug users, or more dependent users, failed to acquire explicit contingency knowledge in the three tests supporting habit theory (tests 9-11), which impaired their devaluation performance, making them appear to be habitual.…”
Section: Human Studiesmentioning
confidence: 99%
“…Indeed, column 7 shows a perfect correspondence between impaired explicit contingency knowledge and impaired devaluation performance. In numerous human learning tasks, explicit knowledge of task contingencies is necessary for accurate performance, that is, participants who have impaired contingency knowledge perform less accurately in these tasks [204][205][206][207][208][209]. The implication is that drug users, or more dependent users, failed to acquire explicit contingency knowledge in the three tests supporting habit theory (tests 9-11), which impaired their devaluation performance, making them appear to be habitual.…”
Section: Human Studiesmentioning
confidence: 99%
“…As we have explained in the introduction, habits reflect stimulusdriven operant behaviors that are characterized by features of automaticity. Research on habit acquisition often relies on using outcome devaluation as a crucial test for establishing the habitual character of a behavior (e.g., Moors et al, 2017;De Houwer et al, 2018). This criterion is of utmost importance when behaviors have previously been reinforced or are still followed by certain outcomes.…”
Section: The Question Of Automaticitymentioning
confidence: 99%
“…Recently, a number of authors have suggested that primarily a decreased influence of the goal-directed network makes people more vulnerable to habitual responding (de Houwer et al, 2018;. Indeed, as discussed before, OFC volume and connectivity appears to be affected in both BN and BED (see section 2.1-2.3).…”
Section: Cognitive Controlmentioning
confidence: 80%